Relationships between body size and physical abilities in elite female tennis players - Skorodumova, A.; Baranov, I. (Coaching and Sport Science Review, 2021)
This paper studied the relationships between anthropometry and physical fitness indicators that affect elite female tennis players` training process planning. Bodyweight and height were measured as well as aerobic and anaerobic lactic capabilities, and the physiological indicators determined. Results showed reliable relationships between the anthropometric and functional fitness indicators and the players` competitive performance. It was concluded that monitoring the average weight relative to the height of female tennis players can assist in the improvement of the players` performance through changes in the training process, specifically by relating the weight and height indicators with the strengths and weaknesses of the players` tactical patterns.